Black Women’s Hair Consciousness and the Politics of Being - Setlaelo, Sarah (Eidos. A Journal for Philosophy of Culture, 2022)
Black women do not want to become white women because they know that this is impossible. Yet, some black women straighten and curl their naturally kinky hair, or wear hair extensions, weaves and wigs that resemble Caucasian hair. Still, they recognize that hair is only one attribute of their Being and that even if they choose to wear non-African hairstyles, they can concurrently embrace other aspects of their black identity. So, is this a matter of cultural assimilation or integration, or is there a deeper ontological problematic underlying these cross-racial hair styling choices? I interrogate three arguments that black women usually advance for their hairstyling choices – the survival strategy argument, the protective styling argument, and the options-choice argument. I use Mabogo Percy More’s interpretation of Jean-Paul Sartre’s concepts of “the Look,” “facticity,” and “bad faith” to analyze Black women’s hair consciousness through the lens of his “Politics of Being” concept.